Altered xanthophyll cycle and fluorescence quenching indicate light-dependent early events in paraquat-treated resistant Erigeron canadensis - Váradi, Gyula (Acta Biologica Szegediensis, 2002)
Violaxanthin de-epoxidation and chlorophyll fluorescence quenching in the presence of paraquat (Pq ) were studied in intact attached leaves of Pq-susceptible (PqS) and Pq-resistan t (PqR) biotypes of Erigeron canadensis under different light conditions. Initially, similar changes were induced in the two biotypes, but the effects relaxed only in the PqR plants, indicating a Pq elimination process. The penetration of Pq in of the chloroplasts of PqR plants proved to be somewhat restricted and highly light-dependent, as revealed by both the light response curves of violaxanthin de-epoxidation and fluorescence quenching and the short-term high-light pre-illumination experiments. An irregular down-regulation of the nonphotochemical fluorescence quenching (NPQ) processes was observed, reflected by lower steady-state zeaxanthin and NP Q levels as compared with the corresponding non-treated high-light controls. It is concluded that light is essential not only forthe initiation of the mechanism of resistance to Pq, but also for the penetration of Pq into the chloroplasts in the PqR E. canadensis. Also, the Pq elimination process may cause a modification to the regulation of the non-radiative energy dissipation in PqR plants in the presence of Pq.